Gender and sexuality ambivalences in danmei narratives: an analysis of the work of Mo Xiang Tong Xiu - Medeiros, Priscila Muniz de; Medeiros, Stéphanie; Ferreira, Rian Paulo (Intexto, 2024)
The paper discusses the work of Chinese author Mo Xiang Tong Xiu, whose novels have been achieving worldwide success. The author’s work is part of a literary genre known as danmei, which focuses on romantic relationships between male characters, commonly produced and consumed by women. The paper begins by exploring the ambivalences of gender and sexuality present in danmei works, as well as discussing the impact of Chinese state censorship on such content. Next, the text seeks to understand how Mo Xiang Tong Xiu’s work incorporates these ambivalences, acting, paradoxically, with the reinforcement and the rupture of gender stereotypes.